You are on page 1of 16

# Integration Worksheet - Substitution Method Solutions

The following are solutions to the Math 229 Integration Worksheet - Substitution Method. Heres
the link to that worksheet http://www.math.niu.edu/courses/math229/misc/int_prac.pdf

Z
1.

(5x + 4)5 dx

(a) Let u = 5x + 4
(b) Then du = 5 dx or

1
du = dx.
5

Z

(5x + 4) dx =
Z
=

u5

1
du
5

1 5
u du
5

1 6
u +C
30
1
(5x + 4)6 + C
=
30

Z
2.

## 3t2 (t3 + 4)5 dt

(a) Let u = t3 + 4
(b) Then du = 3t2 dt
(c) Now substitute
Z

3t (t + 4) dt =
Z
=

u5 du

1 6
u +C
6
1 3
(t + 4)6 + C
=
6
=

Z
3.

4x 5 dx

## Integration Worksheet - Substitution Method Solutions

(a) Let u = 4x 5
(b) Then du = 4 dx or

1
du = dx
4

## (c) Now substitute

Z

Z
4x 5 dx =

1
du
4

1 1/2
u du
4
1 3/2 2
u +C
=
4
3
1
=
(4x 5)3/2 + C
6
=

Z
4.

t2 (t3 + 4)1/2 dt

(a) Let u = t3 + 4
(b) Then du = 3t2 dt or

1
du = t2 dt
3

## (c) Now substitute

Z

t (t + 4)

1/2

(t3 + 4)1/2 t2 dt

u1/2

dt =
=
Z

1
du
3

1 1/2
u
du
3
1 1/2 2
u +C
=
3
1
2 1/2
=
u +C
3
2 3
=
(t + 4)1/2 + C
3
=

Z
5.

cos(2x + 1) dx
(a) Let u = 2x + 1
(b) Then du = 2 dx or

1
du = dx
2
2

## Integration Worksheet - Substitution Method Solutions

(c) Now substitute
Z

Z
cos(u)

cos(2x + 1) dx =
Z
=

1
du
2

1
cos(u) du
2

1
sin(u) + C
2
1
=
sin(2x + 1) + C
2
=

Z
6.

## (a) Let u = sin(x) dx

(b) Then du = cos(x) dx
(c) Now substitute
Z

10

u10 du

1 11
u +C
11
1
=
sin11 (x) + C
11

Z
7.

sin(x)
dx
(cos(x))5

## (a) Let u = cos(x)

(b) Then du = sin(x) dx or du = sin(x) dx

## Integration Worksheet - Substitution Method Solutions

(c) Now substitute
Z

sin(x)
dx =
(cos(x))5

1
sin(x) dx
(cos(x)5
Z
1
(du)
=
u5
Z
=
u5 + C
u4
+C
4
= u4 + C
1
=
+C
(cos(x))4

( x 1)2

dx
8.
x

(a) Let u = x 1
Z

1
1
(b) Then du = dx or 2 du = dx
2 x
x
(c) Now substitute
Z

( x 1)2
1

dx =
( x 1)2 dx
x
x
Z
=
u2 (2 du)
Z
=
2u2 du
2 3
u +C
3
2
=
( x 1)3 + C
3
=

Z
9.
x3 + x2 (3x2 + 2x) dx
(a) Let u = x3 + x2
(b) Then du = (3x2 + 2x) dx

## Integration Worksheet - Substitution Method Solutions

(c) Now substitute
Z

x3

x2

(3x + 2x) dx =
Z
=

u du

u1/2 du

2 3/2
u +C
3
2 3
=
(x + x2 )3/2 + C
3

10.
1

(x2

x+1
dx
+ 2x + 2)3

(a) Let u = x2 + 2x + 2
(b) Then du = (2x + 2) dx du = 2(x + 1) dx or

1
du = (x + 1) dx
2

## (c) If x = 1, then u = (1)2 + 2(1) + 2 = 1

(d) If x = 1, then u = (1)2 + 2(1) + 2 = 5
(e) Now substitute
Z

(x + 1)
dx =
2
(x + 2x + 2)3
=
=
=
=
=
=
=
=

1
(x + 1) dx
+ 2x + 2)3
1
Z 5
1 1
du
3
1 u 2
Z 5
1 3
u du
1 2
5
1 u2
2 2 1
5
1
2
4u 1

 

1
1

4(5)2
4(1)2
1
1

+
100 4
24
100
6
25
(x2

Z
11.

p
cos(x) sin(x) dx

## (a) Let u = sin(x)

(b) Then du = cos(x) dx
(c) If x = 0, then u = sin(0) = 0.
(d) If x = , then u = sin() = 0
(e) Now substitute
Z
0

Z p
p
sin(x) cos(x) dx
cos(x) sin(x) dx =
0
Z 0

=
u du
0
Z 0
=
u1/2 du
0
0
2 3/2
u
=
3
0

 

2 3/2
2 3/2
(0)
=
(0)
3
3
= 0

## f (x) dx = 0. So we didnt actually need to go through the last 5 lines.

Note,
a

Z
12.

(x + 1) sin(x2 + 2x + 3) dx

(a) Let u = x2 + 2x + 3
(b) Then du = (2x + 2) dx du = 2(x + 1) dx or we can write

1
du = (x + 1) dx
2

## (c) Now substitute

Z
Z
2
(x + 1) sin(x + 2x + 3) dx =
sin(x2 + 2x + 3) (x + 1) dx
Z
1
=
sin(u) du
2
Z
1
=
sin(u) du
2
1
= cos(u) + C
2
1
= cos(x2 + 2x + 3) + C
2

## Integration Worksheet - Substitution Method Solutions

3
Z 
1
1
13.
1+
dt
t
t2
(a) Let u = 1 +

1
t

1
1
dt or du = 2 dt
2
t
t
(c) Now substitute
3
Z
Z 
1
1
2 dt =
1+
u3 (du)
t
t
1
= u4 + C
4

4
1
1
=
1+
+C
4
t

(b) Then du =

14.

x2 x3 + 1 dx

(a) Let u = x3 + 1
1
du = x2 dx
3
(c) If x = 1, then u = (1)3 + 1 = 0.

## (d) If x = 1, then u = (1)3 + 1 = 2

(e) Now substitute
Z

x3 + 1 dx =

x3 + 1 x2 dx

1
2

Z
=

Z0 2

=
=
=
=
=

1
du
3

1 1/2
u du
0 3
2
1 3/2 2
u
3
3
2 0
2 3/2
u
9
0

 

2 3/2
2 3/2
(2)
(0)
9
9

2
4 2
8=
9
9

## Integration Worksheet - Substitution Method Solutions

Z
15.

2
dx
3x 7

(a) Let u = 3x 7
(b) Then du = 3 dx or

1
du = dx
3

## (c) Now substitute

Z

dx =
3x 7
=
=
=
=

Z
16.

1

dx
x( x + 1)2
1

(a) Let u = x + 1

1
1
(b) Then du = dx or 2 du = dx
2 x
x

(c) If x = 1, then u = 1 + 1 = 2.

(d) If x = 4, then u = 4 + 1 = 3.

2 1
du
u 3
Z
2 1/2
u
du
3
2 1/2 2
u +C
3
1
4 1/2
u +C
3
4
3x 7 + C
3

## Integration Worksheet - Substitution Method Solutions

(e) Now substitute
Z
1

1

dx =
x( x + 1)2

=
Z2 3
=
=
=
=
=
=

Z
17.
0

1
1

dx
2
( x + 1)
x
1
(2 du)
u2

2u2 du
2
3
u1
2
1 2
3
2

u
 2  
2
2

3
2
2
+1
3
1
3

x
dx
x+1

## (a) Let u = x + 1, then x = u 1 (need this for later)

(b) Then du = dx
(c) If x = 0, then u = 1.
(d) If x = 1, then u = 2

## Integration Worksheet - Substitution Method Solutions

(e) Now substitute
Z 1
0

dx =
x+1

=
Z1 2

=
=
=
=
=
=

Z
18.

u1
du
u
u
1
1/2 du
1/2
u
u

u1/2 u1/2 du
1
2

2 3/2
1/2
u 2u
3
1

 

2 3/2
2 3/2
1/2
1/2
(1) 2(1)
(2) 2(2)
3
3

4 2
2
2 2 +2
3
3
2 2 4
+

3 3
42 2
3

x 2x + 1 dx

1
(a) Let u = 2x + 1. Then x = (u 1) (need this for later)
2
1
(b) Then du = 2 dx or du = dx
2
(c) Now substitute
Z

1
1
(u 1) u du
2
2
Z
1
(u 1) u1/2 du
4
Z
1 3/2 1 1/2
u u du
4
4
1 5/2 2 1 3/2 2
u u +C
4
5 4
3
1 5/2 1 3/2
u u +C
10
6
1
1
(2x + 1)5/2 (2x + 1)3/2 + C
10
6
Z

x 2x + 1 dx =
=
=
=
=
=

10

Z
19.

x x + 1 dx

## You should rewrite the integral as

Z

x1/2

x3/2 + 1 dx

to help identify u.
(a) Let u = x3/2 + 1
2
3
(b) Then du = x1/2 dx or du = x1/2 dx
2
3
(c) Now substitute
Z
x

1/2

x3/2

+ 1 dx =
=
=
=
=
=

Z
20.

Z p
x3/2 + 1 x1/2 dx
Z
2
u du
3
Z
2 1/2
u du
3
2 3/2 2
u +C
3
3
4 3/2
u +C
9
4 3/2
(x + 1)3/2 + C
9

x3 x2 + 1 dx

## (a) Let u = x2 1. Then x2 = u 1 (need this for later)

(b) Then du = 2x dx or

1
du = x dx
2

11

## Integration Worksheet - Substitution Method Solutions

(c) Now substitute
Z
x

Z
x2 + 1 dx =

x2 x2 + 1 x dx

1
(u 1) u du
2
Z
1 3/2 1 1/2
u u du
2
2
1 5/2 2 1 3/2 2
u u +C
2
5 2
3
1 5/2 1 3/2
u u +C
5
3
1 2
1
(x + 1)5/2 (x2 + 1)3/2 + C
5
3

Z
=
=
=
=
=

Z
21.

(x2 + 1) x 2 dx

## (a) Let u = x 2. Then u + 2 = x and (u + 2)2 = x2

x2 = u2 + 4u + 4
(b) Then du = dx
(c) Now substitute
Z
Z

2
(x + 1) x 2 dx =
(u2 + 4u + 4 + 1) u du
Z

=
(u2 + 4u + 5) u du
Z
=
u5/2 + 4u3/2 + 5u1/2 du
2 7/2 8 5/2 10 3/2
u + u + u +C
7
5
3
2
8
10
=
(x 2)7/2 + (x 2)5/2 + (x 2)3/2 + C
7
5
3
=

Z
22.

x2 + 2x
dx
x2 + 2x + 1

(a) First, lets simplify by doing some long division. The work is omitted as I dont know
how to tex long division.
12

## Integration Worksheet - Substitution Method Solutions

1
1
x2 + 2x
=1 2
=1
2
x + 2x + 1
x + 2x + 1
(x + 1)2
Z
1
(b) So we are evaluating 1
dx
(x + 1)2

Z
1

Z
23.

x2

1
1
+C
dx = x +
2
(x + 1)
x+1

1
+ 6x + 9

x2

1
1
=
+ 6x + 9
(x + 3)2

## (b) Rewrite the integral

Z

1
dx
(x + 3)2

(c) Let u = x + 3
(d) Then du = dx
Z

1
dx =
(x + 3)2
=

1
du
u2

u2 du

= u1 + C
= (x + 3)1 + C
1
+C
=
x+3

Z
24.

sec2 (x)
dx
(1 + tan(x))3

## (a) Let u = 1 + tan(x)

(b) Then du = sec2 (x) dx

13

## Integration Worksheet - Substitution Method Solutions

(c) Now substitute
sec2 (x)
dx =
(1 + tan(x))3

1
sec2 (x) dx
(1 + tan(x))3
Z
1
du
=
u3
Z
=
u3 du

1
= u2 + C
2
1
= 2 +C
2u
1
=
+C
2(1 + tan(x))2

Z
25.

sin(x)
dx
(2 + 3 cos(x))2

## (a) Let u = 2 + 3 cos(x)

1
(b) Then du = 3 sin(x) dx or du = sin(x) dx
3
(c) Now substitute
Z

Z
26.

sin(x)
dx =
(2 + 3 cos(x))2

1
sin(x) dx
(2 + 3 cos(x))2
Z
1
1
=

du
u2
3
Z
1
=
u2 du
3
1 1
=
u +C
3
1
=
(2 + 3 cos(x))1 + C
3

x tan(x2 ) sec(x2 ) dx

(a) Let u = x2
(b) Then du = 2x dx or

1
du = x dx
2

14

## Integration Worksheet - Substitution Method Solutions

(c) Now substitute
Z

x tan(x ) sec(x ) dx =

tan(x2 ) sec(x2 ) x dx

Z
tan(u) sec(u)

=
Z
=

1
du
2

1
tan(u) sec(u) du
2

1
sec(u) + C
2
1
=
sec(x2 ) + C
2
=

Z
27.

## (a) Let u = t2 + 4. Then t2 = u 4 (need this later)

(b) Then du = 2t dt or

1
du = t dt
2

Z

3t (t + 4) dt =
Z
=

## 3t2 (t2 + 4)5 t dt

3(u 4)(u)5

1
du
2

3 6
(u 4u5 ) du
2


3 1 7 4 6
=
u u +C
2 7
6
3 7
=
u u6 + C
14
3 2
=
(t + 4)7 (t2 + 4)6 + C
14
=

Z
28.

(tan(2x) + cot(2x))2 dx

(a) Since there isnt an obvious substitution, lets foil and see what happens. This will

15

## Integration Worksheet - Substitution Method Solutions

require some trig identities.
(tan(2x) + cot(2x))2 = (tan(2x) + cot(2x)) (tan(2x) + cot(2x))
= tan2 (2x) + 2 tan(2x) cot(2x) + cot2 (2x)
= tan2 (2x) + 2 + cot2 (2x)
= (sec2 (2x) 1) + 2 + (csc2 (2x) 1)
= sec2 (2x) + csc2 (2x)

(b) The reason we used the trig identities at the end is because we know nice functions whose
derivatives are sec2 () and csc2 ().
(c) Lets rewrite the integral
Z

## sec2 (2x) + csc2 (2x) dx

(d) Let u = 2x
(e) Then du = 2 dx or
(f) Now substitute
Z

1
du = dx
2

## sec (2x) + csc (2x) dx =

=
=
=
=

16

1
(sec2 (u) + csc2 (u)) du
2
Z
1
sec2 (u) + csc2 (u) du
2
1
(tan(u) cot(u)) + C
2
1
(tan(2x) cot(2x)) + C
2
1
1
tan(2x) cot(2x) + C
2
2